Melanocortin 5 Receptor Expression and Recovery of Ocular Immune Privilege after Uveitis. (19th May 2022) - Ng, Tat Fong; Manhapra, Ambika; Cluckey, David; Choe, Yoona; Vajram, Srujan; Taylor, Andrew W.
ABSTRACT: Purpose: The therapeutic use of the RPE-neuropeptide α-MSH suppresses experimental autoimmune uveitis (EAU). This suppression is partially through the α-MSH melanocortin 5 receptor (MC5r). Therefore, we examined the possible role of MC5r-expression in the recovery of RPE suppression of phagolysosome-activation in macrophages following α-MSH-treatment of EAU Methods: The conditioned media of cultured in situ RPE-eyecup from α-MSH-treated EAU wild-type and MC5r(-/-) mice were used to treat macrophages to assay for phagolysosome activation. Results: MC5r(-/-) mice treated with α-MSH recovered from EAU, but with greater retinal damage, and the RPE suppressed phagolysosome activation in wild type but not in MC5r(-/-) macrophages. In addition, α-MSH did not suppress phagolysosome activation in MC5r(-/-) macrophages, and resting-MC5r(-/-) macrophages had augmented phagocytic activity. Conclusion: α-MSH treatment of EAU mediates a MC5r-dependent recovery of RPE suppression of phagolysosome activation in macrophages possibly altering antigen processing and presentation. Also, MC5r-expression helps protect the retina from inflammatory damage. In addition, MC5r-expression is important in the homeostatic maintenance of phagosome-maturation within macrophages.